Freedom of Conscience in Modern Russia: Problem of Personal Security - P. L. Zaitsev; M. A. Sharapova (Сибирское юридическое обозрение, 2015)
The article identifies the problem of spiritual safety of the person, studies the acts regulating rights and freedoms of the person in the religious sphere; the focus is made on the state policy in this sphere. Insufficiency of the taken measures for ensuring spiritual safety of Russians in the conditions of modern distribution and promoting of new religions is emphasized.